The effect of intra‐operative passive movement therapy on non‐surgical site pain after breast reconstructive surgery: a preliminary study1. (22nd May 2014) - Bidd, H.; Dulai, R.; Edelman, N.; Giles, J.; Patel, C.
Summary Pain distant to an operative site is under‐reported but sometimes more severe than pain from the surgical site. Intra‐operative passive movement could possibly reduce this pain. This preliminary study was designed to assess the practicalities of conducting a randomised controlled trial of this therapy in anaesthetised patients. The study design was pragmatic. Forty‐two patients undergoing breast reconstruction were randomly assigned to receive either intra‐operative passive movement or standard care. Twenty‐four hours after surgery, median (IQR [range]) morphine consumption was 33 (11–42 [0–176]) mg in the passive movement group compared with 74 (15–118 [0–238]) mg with standard care (p = 0.126), while participants reported median (IQR [range]) visual analogue scores in areas distant from the surgical site of 0 (0–4 [0–34]) mm in the passive movement group compared with 10 (2–30 [0–57]) mm in those receiving standard care (p = 0.002). A full trial of intra‐operative passive movement therapy to reduce postoperative is feasible and warranted.